Chemically modified carbon nanotubes for use in electroanalysis - Wildgoose, G; Banks, C; Leventis, H; Compton, R (2006)
The discovery of carbon nanotubes has had a profound impact on many areas of science and technology, not least that of electroanalysis. The properties and applications of carbon nanotubes themselves have been well reviewed in the literature and a number of reviews with an electrochemical emphasis have been published. However, the modification of carbon nanotubes has recently been the focus of much research, primarily to improve their solubility in various solvents. Yet modified carbon nanotube electrodes also allow the electrochemist to tailor the properties of the carbon nanotubes, or the electrode surface to impart desired properties such as enhanced sensing capabilities. In this review we attempt to comprehensively cover the different chemical and electrochemical modification strategies and research carried out using modified carbon nanotubes for electroanalytical and bioanalytical applications. Furthermore we also discuss the use of modified carbon nanotubes in electrocatalysis and biocatalysis from an analytical aspect, as well as seeking to dispel some of the myths surrounding the "electrocatalytic" properties of carbon nanotubes. © Springer-Verlag 2005.